Uncovering the other side of fanboys : a study of AKB48 fanboys and their activities in relation to hegemonic gender norms - Er, Michelle Wen Xuan (2013)
The world of idol fanboys has been a largely neglected one even with their increasing visibility due to the recent rise in popularity of mega girl groups such as the Japanese group AKB48. The general public often presumes fan activities as irrational and thus sees it as a feminine activity. Therefore, fanboys are often seen as ‘strange’ for they were not behaving according to hegemonic notions of gender norms where males should be rational at all times. This paper will attempt understand the construction of the identity of fanboys through interviews with 11 AKB48 fanboys. Also, this paper will explore how fanboys negotiate their identity in the face of current stigma and also with their own understandings of gender norms.